ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - Lestari, Eka Puji; Sampurno, R. Djoko (Faculty of Economics and Business Diponegoro University, 2017)
Firm performance is an important part for measuring the success company for being the first thing that will be seen by an investor. This study aimed to analyze the effect of the cash conversion cycle, cash holding, tangible fixed assets, current ratio, leverage, growth, and size on firm performance. Proxy that used to measure firm performance in this study is Return on Assets (ROA).The population in this study are all manufacturing companies listed in Indonesia Stock Exchange for period 2015-2016. Purposive sampling is used to determine the number of samples, 20 companies manufacturing used in this study. The analytical method used is the data panel regression with a significance level of 5% .These results indicate that the cash conversion cycle has significant negative effect on firm performance. Cash holding has insignificant negative effect on firm performance. Tangible fixed assets has significant negative effect on firm performance. Current ratio has significant positive effect firm performance. Leverage significant negative effect on firm performance. Growth significant positive effect on firm performance. Size insignificant negative effect on firm performance. In this study the cash conversion cycle (CCC), holding cash, tangible fixed assets, current ratio, leverage, growth, size are able to explain the firm performance by 94% and the other is explained by other factors beyond research.